The trouble with vampires ebook - Sands, Lynsay (Argeneau, 2019)
Irresistible desire and thrilling suspense combine in this electrifying new Argeneau novel from New York Times bestselling author Lynsay Sands. For close to three thousand years the imposing, impossibly handsome Santo Notte has fought in armies across the world and battled his own, more personal enemies. Of all the places he might expect to encounter his life mate, a quiet corner of upstate New York doesn't seem likely. But as soon as he makes contact with history professor Petronella Stone, while hunting down a suspected rogue immortal, he knows that she will be the greatest adventure of his eternal life. He expects her to be surprised, confused, even overwhelmed. What he doesn't expect is that Pet has a secret history of her own. There's no mistaking the mind-blowing, mutual pleasure they share. But as Pet struggles to protect her nephew from a danger lurking too close to home, Santo realizes there's another threat to her safety—him. And claiming their passionate future will be impossible until he leaves his past behind, forever...